Pengembangan Bahan Ajar Bahasa Indonesia bagi Penutur Asing (BIPA) Melalui Media Kuliner “Nasi Goreng” untuk Mahasiswa Yale University, Amerika Serikat - Fadhila Anna Gunawan; Aprilia Dwi Marlina; Arif Wahyu Nugroho; Ashya Nurvita Mardani; Kundharu Saddhono (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
In this research, we will present a culinary dish in the form of "Fried Rice" which is so well known that it can be used as a teaching material for foreign students in the United States, especially at Yale University. The method used in this research is qualitative research. This method is used to describe students' responses after trying traditional culinary delights, namely fried rice. The BIPA teaching materials created can be adapted to students' ability to speak Indonesian. In the first lesson, the teacher can provide teaching materials using simple language, language that is easy for students to understand. After students can use simple Indonesian, then students will be given teaching materials in a rather complicated language and then teaching materials in a more complex language. In the research "Nasi Goreng" is an excellent choice because of its popularity in Indonesia, as well as the diversity of ways of making it which can reflect Indonesia's diverse culture.